The effect of gut microbiota dysbiosis on patients with preeclampsia - Yefang Zhao; Yefang Zhao; Bingjie Wang; Xiaoling Zhao; Dan Cui; Shaoke Hou; Hongzhen Zhang (Frontiers in Cellular and Infection Microbiology, 2023)
PurposeTo compare the difference of gut microbiota between preeclampsia (PE) and healthy normal pregnant women, providing new therapeutic strategy for preeclampsia.MethodsForty-one PE patients and 45 age- and pre-pregnancy body mass index- matched healthy controls were enrolled from Nov 2021 to May 2022 in this retrospective case-control study. Fecal microbiota was detected by 16S rRNA gene sequencing, followed by bioinformatics analysis including microbial α diversity, microbial β diversity, and linear discriminant analysis effect size (LEfSe) analysis. Serum inflammatory factors were also detected and compared between the two groups.ResultsThere were significant differences in Bacteroidetes (2.68% in PE patients vs 11.04% in healthy controls, P < 0.001), Proteobacteria (4.04% in PE patients vs 1.22% in healthy controls, P = 0.041), and Fusobacteria (1.07% in PE patients vs 0.01% in healthy controls, P = 0.042) between the two groups at the phylum level. Microbial α diversity was lower in PE patients than that in healthy controls. In addition, there was significant difference in microbial β diversity between the two groups. LEfSe analysis showed that there are 24 different taxa between the two groups. The levels of proinflammatory factors including serum tumor necrosis factor-α and Interleukin-6 were statistically significant higher in PE patients than those in healthy controls (both P < 0.001), while there were no significant differences in the levels of serum anti-inflammatory factors including Interleukin-4 and Interleukin-10 between the two groups (P = 0.234 and P = 0.096, respectively).ConclusionPE patients demonstrated gut microbiota disturbances and increasing serum proinflammatory factors, leading to a better understanding of the relationship between the gut microbiota dysbiosis and PE.